Healthy aging in elderly cochlear implant recipients: a multinational observational study - M. Marx (BMC Geriatrics, 2020)
Abstract Background Given an increase in the aging population and its impact on healthcare systems, policy makers for provision of health and social services are aiming to keep older adults in good health for longer, in other words towards ‘healthy aging’. Our study objective is to show that rehabilitation with cochlear implant treatment in the elderly with hearing impairment improves the overall health-related quality of life and general well-being that translate into healthy aging. Methods The multicentre, prospective, repeated measures, single-subject, clinical observational study will accrue 100 elderly, first-time, unilateral CI recipients (≥ 60 years) and analyze changes on specific measurement tools over ca. 20 months from preimplant to postimplant. Evaluations will consist of details collected through case history and interview questionnaires by clinicians, data logging, self-report questionnaires completed by the recipients and a series of commonly used audiometric measures and geriatric assessment tools. The primary indicator of changes in overall quality of life will be the HUI-3. Discussion The protocol is designed to make use of measurement tools that have already been applied to the hearing-impaired population in order to compare effects of CI rehabilitation in adults immediately before their implantation, (pre-implant) and after gaining 1–1.5 years of experience (post-implant). The broad approach will lead to a greater understanding of how useful hearing impacts the quality of life in elderly individuals, and thus improves potentials for healthy aging. Outcomes will be described and analyzed in detail. Trial registration This research has been registered in ClinicalTrials.gov (http://www.clinicaltrials.gov/), 7 March 2017 under the n° NCT03072862 .